The pathway of nitrogen assimilation in Datura stramonium L - Probyn, Trevor Auld (Department of Biological Sciences, 2023)
A survey of the recent literature concerning the assimilation of nitrogen into plant metabolism has been presented. The pathway of nitrate-N assimilation into amino compounds by the leaves and roots of Datura stramonium at different nitrate feeding levels has been investigated using 15N tracer experimentation, enzyme inhibitor studies and enzymological assays. Leaves were fed via their xylem stream with potassium nitrate at -1 -1 two concentration levels: 200 pg. N. ml and 25 JJ8 N. ml , prior to experimentation. Nitrate-15N xylem stream and infiltration feeding experiments on Datura leaves indicate an apparent major routing of newly reduced 15N to glutamine at the high feeding 1 level (200 f8 N. ml-1) and to glutamate at the low feeding level (25 JJ8 N. ml-1). Of the other major soluble amino compounds, serine, glycine, aspartate and alanine were found to be important in the primary assimilation of newly reduced nitrogen. A pre-treatment of the leaves with 5 mM methionine sulphoximine, prior to nitrate-15N infiltration, completely suppressed nitrogen assimilation into amino compounds with the resultant accumulation of 15N in a large ammonia pool. Methionine sulphoximine also caused marked concentration changes in the free amino compound pools, suggesting that conditions of nitrogen stress had been induced. Glutamate dehydrogenase activity (NAD(P)H-dependent) was not inhibited by the methionine sulphoximine pretreatment. Xylem stream feeding of . 15 . ( 15 -1 glutamine- Nat two concentration levels 200 /18 N. ml and